Azlocillin and cefonicid penetration into bone enhanced by probenecid. - Summersgill, J T (1984)
Azlocillin (AZL) and cefonicid (CFD) penetration into rabbit humerus and scapula was evaluated with and without concomitantly administered probenecid. Groups of animals received either 70 mg of AZL intravenously or 20 mg of CFD intramuscularly per kg of body weight; other groups were pretreated with 40 mg of probenecid per kg before the administration of antibiotics. Peak levels of AZL in the sera of animals not receiving probenecid were 76.0 micrograms/ml at 30 min and declined to 7.7 micrograms/ml by 2.0 h. Maximum concentrations in bone were 2.7 micrograms/g in the humerus and 7.1 micrograms/g in the scapula at 1 h. Pretreatment with probenecid significantly elevated levels of AZL in both serum and bone while increasing the half-life in serum from 0.44 to 0.65 h. Maximum drug concentrations in bones of probenecid-pretreated animals were 3.9 and 11.7 micrograms/g in the humerus and scapula, respectively, with detectable levels persisting in bone for up to 4 h. The peak level of CFD alone in serum was 36.7 micrograms/ml at 30 min and declined to 0.86 micrograms/ml at 8 h. Maximum concentrations in bone were 0.66 micrograms/g in the humerus at 1 h and 1.8 micrograms/g in the scapula at 2 h. Pretreatment with probenecid significantly elevated levels of CFD in both serum and bone while increasing the half-life in serum from 1.4 to 2.94 h. Pretreatment with probenecid achieved maximum concentrations of 1.7 and 2.8 micrograms/g in the humerus and scapula, respectively. Detectable levels of CFD persisted in the humerus for up to 4 h and in the scapula for 8 h.